Structure-antimicrobial activity relationship between pleurocidin and its enantiomer - Lee, Juneyoung (Korean Society of Medical Biochemistry and Molecular Biology, 2008)
To develop novel antibiotic peptides useful as therapeutic drugs, the enantiomeric analogue of pleurocidin (Ple), which is a well known 25-mer antimicrobial peptide, was designed for proteolytic resistance by D-amino acids substitution. The proteolytic resistance was confirmed by using HPLC after the digestion with various proteases. To investigate the antibiotic effect of L- and D-Ple, the antibacterial activity and hemolytic effect were tested against human erythrocytes. The D-Ple showed a decreased antibacterial activity and a dramatically decreased hemolytic activity compared with L-Ple. The hemolytic effect of analogue was further confirmed by using calcein leakage measurement with liposome. To elucidate these results, the secondary structure of the peptides was investigated by using circular dichroism spectroscopy. The results revealed that D-Ple, as well as L-Ple, had typical α-helical structures which were mirror images, with a different helicity. These results suggested that the discrepancy of the structure between the two peptides made their antibacterial activity distinct.